Crush'em - Megadeth; Capitol Records (California : Capitol Records, 1999)
Contain the single taken from the album Risk and the Soundtrack Universal Soldier: The Return.
Crush'em (radio edit) / (3:16) -- Crush'em (album version edit) / (4:42).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Film soundtracks; Motion picture music